Long‐Lived Second Near‐Infrared Luminescent Probes: An Emerging Role in Time‐Resolved Luminescence Bioimaging and Biosensing. Issue 2 (15th February 2023) - Feng, Ruibing; Li, Guodong; Ko, Chung-Nga; Zhang, Zhang; Wan, Jian-Bo; Zhang, Qing-Wen
Abstract : Long‐Lived Second Near‐Infrared Probes In the article number 2200131, Qing‐Wen Zhang, Jian‐Bo Wan and co‐workers review the recent process of long‐lived second near‐infrared luminescent probes in time‐resolved luminescent bioimaging and biosensing applications, as well as discuss the present challenges and future directions of these probes in biomedical research, translational research and (pre‐)clinical studies.